Analysis of characteristics and types of infrastructure of innovation laboratories: implications for strategic management (2015)
Abstract. There is a strong emergence of new innovation laboratories all over the world. Past experiences have shown these types of projects are at risk to not succeed in their goals. The physical space is considered as a conscious asset to improve the innovation outcomes that must be carefully designed according with the strategic goals of the project. Throughout this work, five frameworks from the literature that analyze innovation laboratories are identified and compared. Then, based on both literature and authors’ experience, an updated framework is proposed as basis for a guidance tool for researchers and practitioners aiming to adapt or to start a new laboratory. As part of the operationalization process of the framework, a preliminary maturity grid is built and from there a questionnaire is designed. Afterwards, an international study with answers from ten laboratories from five different countries is done. As result and main contribution from this work researchers and practitioners will find a comprehensive set of practices and experiences in the way innovation laboratories have been implemented and operated in order to build their own strategy.